1999
DOI: 10.2166/wst.1999.0329
|View full text |Cite
|
Sign up to set email alerts
|

Complementary independent molecular, radioisotopic and fluorogenic techniques to assess biofilm communities in two wastewater wetlands

Abstract: Optimisation of nutrient removal processes requires a detailed understanding of the microbial physiologies actually occurring within the biomass of different treatment zones, and also knowledge of how these communities respond to environmental factors. This paper describes a suite of four independent and complementary, microbiological techniques, utilised to obtain detailed assessments of wastewater bacterial biomass. Examples of these techniques are shown as applied to biofilms from two surface-flow wetlands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…3). These percentages, like the b/g ratio variation, were similar to those reported by Flood et al (1999) in a FWS biofilm, showing a decrease in b (62 to 41%) and an increase in g (11 to 34%) from the inlet to the outlet of a wetland, respectively. In our system, the b/g ratio evolved from a 3 : 1 value in the influent to 7 : 1 in the SP effluent, decreasing to the initial proportion in the final effluent.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…3). These percentages, like the b/g ratio variation, were similar to those reported by Flood et al (1999) in a FWS biofilm, showing a decrease in b (62 to 41%) and an increase in g (11 to 34%) from the inlet to the outlet of a wetland, respectively. In our system, the b/g ratio evolved from a 3 : 1 value in the influent to 7 : 1 in the SP effluent, decreasing to the initial proportion in the final effluent.…”
supporting
confidence: 87%
“…Previous works on wetlands have focused on the biofilm communities during summer with different results. Flood et al (1999) found 12 and 4% NEU in the inlet and outlet parts, respectively, of a low loaded wetland. Silyn-Roberts and Lewis (2001) studied a wetland as a tertiary treatment of a dairy effluent and the percentage of NEU in the biofilm fluctuated from 0 to 1.5%.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…An easy and often used method is the reduction of CTC by the respiratory electron transport chain to insoluble, fluorescent formazan crystals (CTF). This method is commonly applied to determine respiratory activity and viability of bacteria in many different complex microbial systems (4,6,13). However, several studies indicate that this method is unable to detect all active cells and thus underestimate the real number if it is compared to the other two methods (e.g., references 6 and 14).…”
mentioning
confidence: 99%